Review of Evaluation Journal of Australasia: Volume 6, No. 1 - Wes Martz (Journal of MultiDisciplinary Evaluation, 2007)
Editors Rosalind Hurworth and Delwyn Goodrick include four refereed articles, two book reviews, and the keynote address from the AES 2005 International Conference in this issue of the Evaluation Journal of Australasia.